SUSTAINABLE RANGELAND MANAGEMENT ON THE TERRITORY OF THE STATE FOREST FUND IN KYRGYZSTAN: PROBLEMS AND OPPORTUNITIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The forests of Kyrgyzstan, despite their small area, play an important role in ecological, social and economic terms, especially for the local population. Forests are state-owned,mainly managed by the State Forest Fund, and cover 2,613,740 ha, of which 1,123,050 ha (5.62%of the total area of the country) are forested. About 1.2 million ha are used for grazing, makingpastoralism one of the main rural activities. However, regardless of the form of ownership, pasturedegradation due to increased livestock numbers, overgrazing and mismanagement is a widespreadproblem with serious consequences for both livestock production and the environment.
Keywords: forest pastures, overgrazing, pasture degradation, grazing planning.